Should Income Inequality be Praised? Multiple Public Goods Provision, Income Distribution and Social Welfare - Jun-ichi Itaya; Atsue Mizushima (Center for Economic Studies and ifo Institute (CESifo), 2016)
We investigate how income inequality affects social welfare in a model of voluntary contributions to multiple pure public goods. Itaya, de Meza, and Myles (1997) show that the maximization of social welfare precludes income equality in a single pure public good model. In contrast, we show that the result of Itaya et al. may not be valid in a case of multiple voluntarily supplied public goods; specifically, we show that not only an income inequality-raising redistribution policy but also an income-equalizing one may raise social welfare. We also show that if altruistically motivated voluntary transfers are allowed, an inequality-raising redistribution policy is no longer effective and leaves social welfare unchanged.
Keywords: D31; D63; D64; H23; H31; 330; public goods; inequality; social welfare; voluntary provision; income distribution